SECONDARY EDUCATION IN THE USA: THE RETROSPECTIVE ANALYSES OF LEGISLATION - Nikolska, Nina (Studies in Comparative Education, 2020)
The purpose of the article is to analyze the key laws in education that over the past decades have shaped the educational policy of the United States. It was revealed that the result of the American educational policy is that today the average graduate ratings are the highest, the rate of decline is minimal. These achievements provide a solid foundation for further work to expand educational opportunities and improve learning outcomes. It is concluded that the current legislation forms the guidelines for the development of modern American education, structuring it according to trends, such as improving quality by optimizing accountability at all levels and ensuring equal access to quality education by introducing special programs at the federal and state levels. Educational policy in the United States is focused on meeting the individual and national needs of society. A quality education for every child depends on highly qualified teachers who keep students at a high level, on a regular assessment to see what works and what doesn’t. It depends on the parents involved, armed with choice and information. Today we see a new striving for excellence, caused by the Law “No Child Left behind Act”. Of course, there are new problems. Students' interest in science and technology is declining as other countries seek to fill this gap. But for the first time in a long time, America considers itself responsible for the results. Thanks to significant federal and state-level reforms and innovations at the state and local levels, education in the United States is constantly evolving and growing. The country seeks to help children unleash their high potential, both individuals and citizens in a world where freedom is on the verge.